Emerging targeted therapies in oral oncology: Focus on EGFR inhibition - Vishnu Priya Veeraraghavan; Shikhar Daniel; Arun Kumar Dasari; Kaladhar Reddy Aileni; Chaitra patil; Santosh R. Patil (Oral Oncology Reports)
This comprehensive study explored the role of epidermal growth factor receptor (EGFR)-targeted therapies in oral cancer, focusing on emerging strategies, challenges, and future directions. The EGFR signalling pathway plays a critical role in the development and progression of oral cancer, making it an attractive therapeutic target. Small-molecule tyrosine kinase inhibitors (TKIs) and monoclonal antibodies (mAbs) targeting EGFR have shown promise in preclinical studies and clinical trials. However, challenges, such as the development of resistance mechanisms and treatment-related toxicities, pose obstacles to their clinical utility. Future directions in EGFR-targeted therapy include the exploration of combination therapies and the identification of predictive biomarkers to optimize treatment strategies and improve patient outcomes in oral cancer.